"Casifore" Sabun Cair 2 In 1, Berbahan Alami Dari Ekstrak Ampas Teh Dan Ekstrak Daun Adas - Faizah, Kayla Jihan; Syifa , Khairunnisa; Banoen, Dzakiyyah (Jurnal Inovasi Daerah, 2025)
Soap can protect the skin from bacteria. The addition of natural ingredients that are safe for health can provide a distinctive aroma. Given the abundant availability of natural materials, a study was conducted on the production of liquid soap mixed with natural extracts. The production of this 2-in-1 liquid soap, functioning both as hand soap and dishwashing soap, utilized tea dregs waste and fennel leaves as active ingredients. The purpose of this research was to determine the best formulation of liquid soap from tea dregs extract and fennel leaf extract, the potential of liquid soap as a 2-in-1 product (hand soap and dishwashing soap), consumer preference level, and the cost analysis of producing the 2-in-1 liquid soap. This study was experimental research applying the production of liquid soap from tea dregs extract and fennel leaf extract, with five treatments: P1 = 15 ml fennel leaf extract; P2 = 5 ml tea dregs extract + 10 ml fennel leaf extract; P3 = 7.5 ml tea dregs extract + 7.5 ml fennel leaf extract; P4 = 10 ml tea dregs extract + 5 ml fennel leaf extract; P5 = 15 ml tea dregs extract. This research was carried out in January 2025 at the Industrial Chemical Engineering Laboratory and the Agricultural Product Quality Control Laboratory. Based on the results, treatment 2 was found to be the best. The test results of liquid soap in treatment 2 were: pH 7.0, specific gravity 1.117 g/ml, viscosity 726 cPs, insoluble material in ethanol 0.4, free fatty acids 0.89, microbial contamination < 10 colonies/g, and in accordance with SNI st Ahwan, dan Qonitah, F., 2018, Pengaruh Pemberian Ekstrak Etanol Daun Adas terhadap Kadar Hormon Prolaktin pada Tikus Betina Post Partum, Jurnal Farmasetis, 8 (1): 39-44 Debnath, B; Haldar, D ; Purkait 2021. Potential and sustainable utilization of tea waste: A review on present status and future trends. Journal of Environmental Chemical Engineering 9 (6):106179. http://doi.org/10.1016/j.jece.2021.106179. Ghandy, 2012. Surfaktan (http://nanjatogawa.blogspot-.com/2012/03/ surfaktan.html, diunduh 3 Maret 2014). Karneng, S. (2023). Pelatihan Pembuatan Sabun Cuci Piring Berbahan Dasar Daun Sirih Dan Daun Binahong Sebagai Upaya Pemberdayaan Ibu-Ibu PKK. Jurnal Solma, 12(1), 283–293. https://doi.org/10.22236/solma.v12i1.11304 Kridati, E. M., E. Prihastanti dan S. Haryanti. 2012. Rendemen Minyak Atsiri dan Diameter Serta Ukuran Sel Minyak Tanaman Adas (Foeniculum vulgare Mill) yang Dibudidayakan di Kabupaten Semarang dan Kota Salatiga. Buletin Anatomi dan Fisiologi. 20(1): 1-17 Kusumaningrum R, Supriadi A, Hanggita S. 2013. Karakteristik dan mutu teh bunga lotus. Jurnal Fishtech. 2(1): 9-21. Rabiah, S. (2018). Penggunaan metode Research and Development dalam penelitian Bahasa Indonesia di perguruan tinggi. Septianingrum, E. Rahmawati; Faradilla, R.H. Fitri; Ekafitri, Riyanti; Murtin, Susantika; Perwatasari, dan D. Dian. 2009. Kadar Fenol dan Aktivitas Antioksidan pada Teh Hijau dan Teh Hitam Komersial. Artikel PKM. Institut Pertanian Bogor. Bogor. Suryaningrum, D.A., Ningrum, A.W., Slamet, dan Rahmatullah, S., 2013, Aktivitas Antibakteri Sabun Cair Estrak Etanol Daun Adas (Foeniculum vulgare Mill.) terhadap Stapylococcus aureus ATTC 25923, Health Science and Pharmacy Journal: 1-8 Utami, P., Puspaningtyas, D. E., & Gz, S. (2013). The miracle of herbs. Jakarta: AgroMedia. Widiati S. 2011. Daya hambat ekstrak ampas teh hitam (Camellia sinensis) terhadap pertumbuhan Staphylococcus epidermidis [Skripsi]. Yogyakarta (ID): Fakultas Teknobiologi, Universitas Atmajaya Yogyakarta. Widyasanti, A., Winaya, A. T., & Rosalinda, S. (2019). Pembuatan Sabun Cair Berbahan Baku Minyak Kelapa Dengan Berbagai Variasi Konsentrasi Ekstrak Teh Putih. Agrointek, 13(2), 132–142. Zaini, M.S.M. and Syaf, W.A, 2021. Recycling of Waste Tea Leaves via Vermicomposting Process and the Effect on Water Spinach Growth. Kem. Ind. 70 (7-8): 387−392, https://doi.org/10.15255/KUI.2020.065 andards. Based on the preference test, respondents generally liked the product with an average preference score of 3.60. The cost analysis showed that the production of this liquid soap was profitable, with an R/C ratio of 1.39.